Fundamental flow-path design, optimization and numerical analysis of flow in axial turbines - Hu, Heng (Institutionen för värme- och kraftteknik, Tekniska högskolan i Lund, 2025)
The current study presents a comprehensive research on the design, optimization, and numerical analysis of axial turbines, addressing the urgent need for more efficient and environmentally friendly energy conversion systems. With turbines being central to power generation, aviation, and marine propulsion, enhancing their performance is crucial to reducing fuel consumption, operational costs, and greenhouse gas emissions. The research integrates classical thermodynamic theories with advanced computational methods to create optimized turbine designs capable of meeting modern energy demands.
Keywords: turbine design; aerodynamic performance; blade optimization; surface curvature